Risk factors of postoperative delayed wound healing in patients with rheumatoid arthritis treated with a biological agent. Issue 3 (4th May 2021) - Okita, Shunji; Ishikawa, Hajime; Abe, Asami; Ito, Satoshi; Nakazono, Kiyoshi; Murasawa, Akira; Nishida, Keiichiro; Ozaki, Toshifumi
Abstract: Objectives: This retrospective study aimed to investigate the risk factors associated with delayed wound healing (DWH) after orthopedic surgery in rheumatoid arthritis (RA) patients treated with biological disease-modifying antirheumatic drugs (bDMARDs). Methods: We reviewed medical records of 276 orthopedic procedures for 187 RA patients treated with bDMARDs. As a preoperative nutritional status assessment, we evaluated body mass index, prognostic nutritional index (PNI), and controlling nutritional status (CONUT). We evaluated DAS28-CRP, DAS28-ESR, face scale, global health, and HAQ-DI to assess the disease activity. Univariate and multivariate logistic regression analyses were performed to evaluate the risk factors for DWH. Results: In 276 procedures, DWH was identified in 24 patients (8.7%). Disease duration, foot and ankle surgery, and preoperative use of tocilizumab were significant in the univariate analyses. These variables were entered into a multivariate model, and it was revealed that preoperative use of tocilizumab and procedures in the foot and ankle were associated with an increased risk of DWH. Conclusion: The current retrospective study suggested that preoperative use of tocilizumab and procedures in the foot and ankle were risk factors for DWH.